Cowden syndrome with bronchial asthma - Özsürekci, Yasemin; Yavuz, Süleyman Tolga; Alanay, Yasemin; Ütine, Gülen Eda; Kalaycı, Ömer (The Turkish Journal of Pediatrics, 2010)
Cowden’s syndrome (CS) is a rare autosomal dominant disorder characterized by multiple hamartomas and an increased risk of breast, thyroid and endometrial carcinomas. Mutations of tumor suppressor gene PTEN (phosphatase and tensin homolog) on chromosome 10p23.2, which encodes a lipid phosphatase mediating cell cycle arrest and apoptosis, were first described in CS. Some studies have also implicated PTEN in the pathogenesis of bronchial asthma. Herein, we describe a boy with CS referred to the pediatric allergy unit with bronchial asthma symptoms. This patient is one of the very few reported cases with CS with lung disease and possibly the first with bronchial asthma.